Application of Artificial Intelligence in Academic Libraries - Antonija Marinclin; Robert Idlbek; Miroslav Popović (Bosniaca)
Objective: This paper aims to explore the current state of artificial intelligence (AI) applications in academic libraries in Croatia and its potential impact on library services. It seeks to present the challenges and opportunities in AI implementation and the factors that may influence its adoption. Methodology: To research the application of AI in academic libraries, a mixed-method approach, combining quantitative and qualitative data collection techniques, was employed. Specifically, an online survey consisting of 21 open- and closed-ended questions was conducted. The survey targeted academic libraries in Croatia to gather comprehensive data on the current state of AI implementation. Results: The research showed a low response rate to the survey, with only 22%, as AI implementation in Croatian academic libraries is still in its early stages. The results revealed that barriers such as a lack of funding, expertise, and institutional support hinder wider adoption, along with concerns about AI’s impact on critical thinking and human roles. The lack of training and strategic planning around AI oversight may have contributed to the low response rate, complicating the drawing of firm conclusions. However, the survey did indicate the potential for AI use in the surveyed higher education libraries, as they recognise its possible benefits in work processes and user experiences. Originality: This study is among the first to explore the current state and future implications of AI adoption in academic libraries in Croatia. It provides insights into the challenges and opportunities of AI implementation and its potential impact on library services in the country.